2003
DOI: 10.2527/2003.81suppl_311x
|View full text |Cite
|
Sign up to set email alerts
|

Management of photoperiod in the dairy herd for improved production and health

Abstract: Environmental influences on lactation efficiency are frequently associated with reductions in milk output. Heat stress, for example, leads to depressed feed intake and, subsequently, losses in production. Conversely, cold stress may limit nutrients available for milk synthesis. Fortunately, one environmental factor, photoperiod, can exert a positive effect on dairy performance when managed properly. Long days have consistently been shown to improve milk yield during established lactation. In addition, photoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 42 publications
5
55
0
2
Order By: Relevance
“…Another possible factor influencing the percentage of fat and protein in the milk is the level of milk yield. As is well known, milk yield is affected by photoperiod and increases in correlation with increasing day length (Stanisiewski et al, 1985;Dalh and Petitclerc, 2003); it is therefore plausible to believe that for the latitudes considered in this study, the reduction in milk components recorded in spring might be related to the increase in milk yield as a response to the increasing photoperiod, with a consequent dilution effect on protein and fat concentrations. The higher milk yield in spring in the study area is testified by official statistic data (www.CLAL.it).…”
Section: Discussionmentioning
confidence: 70%
“…Another possible factor influencing the percentage of fat and protein in the milk is the level of milk yield. As is well known, milk yield is affected by photoperiod and increases in correlation with increasing day length (Stanisiewski et al, 1985;Dalh and Petitclerc, 2003); it is therefore plausible to believe that for the latitudes considered in this study, the reduction in milk components recorded in spring might be related to the increase in milk yield as a response to the increasing photoperiod, with a consequent dilution effect on protein and fat concentrations. The higher milk yield in spring in the study area is testified by official statistic data (www.CLAL.it).…”
Section: Discussionmentioning
confidence: 70%
“…The seasonal effect was partly due to richer winter feed during a period that is more representative of lactation than winter or spring calving. Increasing the photoperiod also helped to improve milk production (Dahl and Petitclerc, 2003), but did not seem to counteract the feeding effect of spring calving.…”
Section: Analysis Of Second Lactationmentioning
confidence: 94%
“…According to Nianogo et al (1991), this effect is not only due to the type of feeding in early lactation, but can also stem from other factors such as heat stress or photoperiod (Dahl and Petitclerc, 2003). In Israel, Barash et al (1996) found that milk production was stimulated by autumn calving and reduced by spring calving; these observations are hard to explain in physiological terms and more research is needed.…”
Section: Introductionmentioning
confidence: 99%
“…As will be discussed in a later section of this chapter, exposure of lactating dairy cows to long day photoperiod (16h light; 8h dark) increases milk production, and exposure of late-pregnant cows to short day photoperiod (8h light; 16h dark) increases milk production in the subsequent lactation Dahl & Petitclerc, 2003). It was initially thought that this effect was mediated by melatonin.…”
Section: Melatoninmentioning
confidence: 99%